THE RELATION OF ALCOHOL CONSUMPTION WITH CARDIOVASCULAR DISEASES AND RISK FACTORS (ESSE-RF TRIAL IN KEMEROVSKAYA OBLAST) - S. A. Maksimov; Ya. V. Danilchenko; M. V. Tabakaev; T. A. Mulerova; E. V. Indukaeva; G. V. Artamonova (Российский кардиологический журнал, 2017)
Aim. To analyze the relation of alcohol consumption level with cardiovascular diseases and risk factors in the population of Kemerovskaya Oblast.Material and methods. The study was performed under the framework of multicenter epidemiological trial ESSE-RF in Kemerovskaya Oblast, with 1628 participants with the age 25-64 y.o. The data was analyzed concerning the prevalence, volume and type of alcohol beverages by the respondents, as the prevalence of a range of cardiovascular diseases and risk factors. By original formulae, total volume was calculated of the consumed alcohol in units of the “safe” ethanol dose (24 grams) with further grouping to “non consuming” and consuming “moderately”, “in-between” and “over”.Results. Overconsumption of alcohol, comparing to non-consumers, is associated with high risk of hypercholestrolemia (OR 1,76; 95% CI: 1,12-2,75), hypertriglyceridemia (OR 2,69: 1,52-4,77), body overweight (OR 1,68: 1,04-2,71), smoking (OR 2,24: 1,48-3,41). The relation of low physical activity with alcohol consumption is found in all grades. Increase of the mean daily ethanol dosage is positively linearly related with the risk of arterial hypertension (OR 1,04: 1,11-2,75), hypercholesterolemia (OR 1,06: 1,01-1,12), increased level of low density lipoproteins (OR 1,09: 1,02-1,16), smoking (OR 1,17: 1,10-1,24), low physical activity (OR 1,09: 1,02-1,16). There is U-shaped and upside-down J-shaped relation for the level of psychological risk factors (stress, anxiety, depression) and volumes of consumed alcohol. By the considered cardiovascular diseases it can be noted only, the existence of statistically non-significant (0,1>р>0,05) tendency to decrease myocardial infarction risk and stroke in anamnesis, with the increase of the consumed alcohol volumes comparing to non-drinkers.Conclusion. The study shows that overconsumption of alcohol, as the increase of mean daily dosage of ethanol are associated with the range of cardiovascular risk factors. There is U-shaped and upside-down J-shaped relation of psychoemotional risk factors with the volumes of consumed alcohol. By the considered cardiovascular dseases, there are no significant relations for the level of consumed alcohol, however, there is non-significant tendency for myocardial infarction and stroke risk factors diminishing in the anamnesis, with the increase of consumed alcohol volumes.